Analysis of Spontaneous Subpeak Emission from the Guide Layers of the Ultraviolet‐B Laser Diode Structure Containing Composition‐Graded p‐AlGaN Cladding Layers. Issue 14 (24th January 2020) - Sato, Kosuke; Yasue, Shinji; Ogino, Yuya; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract : This article covers an investigation of the optical properties and the origin of the mechanism of spontaneous subpeak emission from an ultraviolet‐B (UVB) light‐emitting diode containing aluminum gallium nitride (AlGaN) guide layers, by changing the p‐electrode size and AlGaN film structure. The subpeak emission originates from the guide layer above the quantum well. Moreover, the ratio of the output power of the well emission to the total output power depends on the current density. This ratio increases with increasing current density. The estimated mechanism of the subpeak emission is the electron overflow to the second guide layer and carrier recombination at the interface of the AlGaN guide and AlGaN electron blocking layers (EBLs). The larger difference in the Al/III molar ratio at the interface of the guide layer and the EBL in the UVB laser diode (LD) is considerably larger than that of the layers in conventional visible LDs containing bulk p‐AlGaN. Because of this difference in molar ratios, a deeper energy valley is formed to assist the unfavorable carrier recombination. Abstract : The mechanism of the spontaneous subpeak emission from the ultraviolet‐B (UVB) light‐emitting diode containing composition‐graded p‐AlGaN cladding layers is estimated as the electron overflow to the second guide layer and carrier recombination at the interface of the AlGaN guide and AlGaN electron blocking layers with a deeper energy valley than the conventional visible laser diode (LD).